Stability of Ternary Drug–Drug–Drug Coamorphous Systems Obtained Through Mechanochemistry - Ilenia D’Abbrunzo; Elisabetta Venier; Francesca Selmin; Irena Škorić; Enrico Bernardo; Giuseppe Procida; Beatrice Perissutti (Pharmaceutics)
Background/Objectives: This study investigates the preparation of coamorphous systems composed entirely of active pharmaceutical ingredients (APIs), namely praziquantel, niclosamide, and mebendazole. The objective was to formulate and characterize binary and ternary coamorphous systems to evaluate their structural, thermal, and stability properties. Methods: Ten different mixtures (binary and ternary) were designed through a mixture design approach and prepared using a sustainable, one-step neat grinding process in a lab-scale vibrational mill. The systems were prepared reproducibly within 4 h across the entire experimental domain. Structural characterization was performed using PXRD and FTIR to confirm the absence of crystalline domains and the presence of molecular interactions. The glass transition temperature (Tg) was theoretically calculated using the Gordon–Taylor equation for three-component systems and determined experimentally via DSC. Stability studies were conducted on seven systems under different storage conditions (−30 °C, 5 °C, 25 °C, and 40 °C) for six months. Results: PXRD analysis confirmed the formation of coamorphous systems with no crystalline phases. DSC revealed a single Tg for most systems, indicating homogeneity. Stability studies demonstrated that five out of seven systems adhered to the “Tg—50 °C” stability rule, remaining physically stable over six months. Recrystallization studies indicated diverse pathways: some systems reverted to their original crystalline phases, while others formed new entities such as cocrystals. Conclusions: This study highlights the feasibility of coamorphous systems composed of multiple APIs using a simple, solvent-free grinding approach. The findings underscore the importance of molecular interactions in determining stability and recrystallization behavior, offering insights for designing robust coamorphous formulations.